Factors influencing the Internet of Things (IoT) implementation in fieldwork courses / Fatin Khairuddin ... [et al.] - Khairuddin, Fatin; Boll Kassim, Nur Qursyna; Othman, Hamizah; Wan Ahmed, Wan Natasya; Adam, Salwa; Aani, Siti Nur Anisah; Mohd Noor, Nuraini (Universiti Teknologi MARA, Kedah, 2024)
The integration of Internet of Things (IoT) technologies into education needs to be effectively harnessed to complement the learning process and cultivate industry-ready graduates. This study aims to identify the critical factors influencing the implementation of IoT in fieldwork courses and to determine the relationship between these factors and IoT implementation. A sample of 156 students was randomly selected from 250 undergraduate students enrolled in the fieldwork courses at the Faculty of Plantation and Agrotechnology, UiTM Melaka Branch, Jasin Campus, UiTM, Malaysia. Data were collected using a close-ended questionnaire and analysed for descriptive statistics, multiple regression analysis, and correlation analysis using SPSS version 27. The results showed that all factors significantly influenced the implementation of IoT in fieldwork courses (p-value < 0.05). Multiple regression analysis indicated that the most critical factor is curriculum alignment (p-value < 0.05; standardised β-value = 0.634), compared to faculty development and training, infrastructure and resources, and industrial collaboration, with a strong correlation between the variables (R = 0.722). The R² value of 0.521 indicates that 52.1% of the dependent variable (implementation of IoT) is explained by the independent variables, while 47.9% is explained by non-studied factors. All factors have a linear positive relationship with IoT implementation (p-value < 0.05). Based on the factors identified in this study, it is suggested that subsequent research should emphasise the integration of IoT into curriculum alignment to enhance learning experiences and align curricula with evolving industry demands.